Novel in vivo Assessment of Unruptured Intracranial Aneurysm Inflammatory Factors - Cordina, Steve M.; Afarian, Shant; Gerthoffer, William T.; Martino, Anthony; Wilson, Russell; Naritoku, Dean K. (Frontiers in Neurology, 2020)
Background and Purpose: The growth and eventual rupture of intracranial aneurysms may be due to an underlying inflammatory process as evidenced by pathological examination of aneurysm walls. We hypothesize that unruptured aneurysms have an increased inflammatory milieu within their lumen in comparison to the rest of the cerebral arterial vascular system. Methods: Blood was sampled from unruptured aneurysms in patients presenting for aneurysm coil embolization and C3 and C4 complement values from this serum were compared with complement values in the parent artery. Results: Ten patients were enrolled over 32 months, with a mean aneurysm size of 9.1 mm. Compared to control samples drawn from peripheral circulation, there were significant decreases of both C3 (p=0.0003) and C4 (p=0.0063) levels in aneurysmal blood samples. Conclusions: A state of decreased complement indicative of classic pathway activation was found in all tested aneurysms, thus providing evidence of an ongoing process of complement activation in the blood of live unruptured aneurysm sacs.